Clerodendrum hendersonii (Verbenaceae), an addition to the flora of Gunung Ulu Kali, Malaysia - Kiew, Ruth (Malaysian Nature Society, 1989)
Clerodendrum hendersonii, a Peninsular Malaysian endemic previously known only from Cameron Highlands, is reported from Gunung Ulu Kali, Pahang. It is distinguished from C. colebrokianum, an Indian species, which was incorrectly reported from Singapore by Lobb.